Study the development of touristic demand in Syria - Dayoub, M.M.; Tayoub, Mahmoud; Mansour, W. (Latakia University Journal - Economic and Legal Sciences Series, 2019)
سوريا مهد الحضارات وأم الأبجدية، تمتلك مواقع أثرية وإمكانات تجعلها قبلة السائحين، ومع تطور الصناعة السياحية وتزايد فاعليتها في تنشيط الاقتصاد الوطني، لم تعد هذه الصناعة مجالاً لتجارب الخطأ والصواب، بل عملاً علميا ًواعياً يهدف إلى تحقيق الاستثمار الأمثل للإمكانات المتاحة بما يتوافق مع خطط التنمية. هذا البحث يلقي نظرة تحليلية لواقع الطلب السياحي في سوريا ، من خلال إبراز الواقع الحالي والتنبؤ بالطلب المستقبلي والمساهمة في رسم السياسات المتعلقة بقرارات الاستثمار عن طريق دراسة تطور الطلب أعداد القادمين والسياح(النزلاء) والليالي السياحية والتغيرات الطارئة عليها. Syria is the center of civilization and the mother of the alphabet. The archeological and touristic sites attract tourists .With the development of touristic industry and increasing its role in active national economy, touristic industry is not area trial and error, but the conscious scientific job for achieving optimum investment of the available sources associated with development plans. This article is an analytical study of the touristic demand in Syria, for activating the touristic movement through the current situation and forecasting the demand and contribution to the related policies through the study of the number of tourists, and touristic nights and their casual changes.